Pengaruh Kompetensi Kepala Sekolah dan Sarana Prasarana Terhadap Kinerja Guru SMK Negeri di Kota Palembang - Yuniarti Yuniarti; Jumadi Walajro (Universitas Palangka Raya, 2024)
The level of teacher performance in carrying out their main duties at school is greatly influenced by the competence of the school principal and the completeness of school facilities. This research aims to statistically measure the influence of the competence of school principals and the completeness of school facilities on the performance of vocational school teachers in Palembang City. To achieve this goal, a quantitative research design with a correlative approach was used. The research population was 55 teachers who served in three vocational schools in Palembang City. The research instrument was validated using Pearson Product Moment, and data reliability was verified using the Cronbach Alpha test. The research results reveal that (1) the principal's competence is related to teacher performance, and the principal's competence has minimal influence on the performance of vocational school teachers. (2) Facilities and infrastructure were found to be related to vocational school teacher performance. Facilities and infrastructure have a significant effect on the performance of vocational school teachers. (3) The competence of the school principal, facilities and infrastructure have a significant influence on the performance of vocational school teachers. The competence of school principals, facilities and infrastructure also have a minimal impact on the performance of vocational school teachers.